IoT based monitoring system for mobility control of dairy cattle in Indonesia - Sofiyanti Indriasari; Aditya Wicaksono; Yuni Resti; Dudi Firmansyah; Arvy Adhitya Sutisna (Penerbit Universiti Kebangsaan Malaysia, 2023)
Providing appropriate space for movement is one of the best ways needed to increase cows’ comfort in optimizing their productivity. Currently, several farms have made some changes to the housing system by implementing a free-stall housing system. The system makes the cows more comfortable to rest and do activities because they are not tied up. Due to the large number of cows that are kept, sometimes farmers find it difficult to detect the health condition of each cow individually. Hence, an early detection system is needed to control and monitor cattle activity. The study aimed to develop a monitoring system at the free stall barn farm based on the internet of things. The method used for the study adopted the steps in the System Development Life Cycle (SDLC). Microcontroller-based dairy cow mobility monitoring tool built with NodeMCU ESP8266, GPS sensor, 5v booster, 18650 battery and housing to protect all components. All components used cables with the provisions of the NodeMCU ESP8266 as the tool control centre, GPS sensor as a coordinate point reader, battery as a voltage source, and 5v voltage booster as a component that controls the tool and controls the power off or on. The tool works by getting a power source from the battery and then displaying all the components. The GPS antenna will search for satellites to determine the coordinates of the tool and the coordinate point information will be sent to the NodeMCU ESP8266. When the GPS antenna searches for coordinates, the NodeMCU ESP8266 will look for a WiFi connection in it to then be able to access the internet and send information from the GPS sensor to the hosting website.